Association of the carriage of IL-1B rs1143634 and rs16944 polymorphisms and BDNF rs6265 polymorphism with temporal lobe epilepsy - Yu. S. Panina; D. V. Dmitrenko; N. A. Shnaider; E. V. Egorova; A. A. Usoltseva (Неврология, нейропсихиатрия, психосоматика, 2019)
Temporal lobe epilepsy (TLE) is one of the most common and refractory forms of epilepsy, which has different etiologies. Experimental and clinical studies have demonstrated that transformation of the normal brain neuron activity pattern into paroxysmal one is accompanied by changes in the expression of cytokines and neurotrophins in the hippocampus and temporal cortex. Modulation of the expression of brainderived neurotrophic factor (BDNF) may be associated with the carriage of the single nucleotide polymorphism (SNP) rs6265 in the BDNF gene. Groups of investigators have shown the increased expression of BDNF in the hippocampus and temporal cortex of patients with drugresistant epilepsy. Independent studies have demonstrated the role of the IL-1B gene encoding the proinflammatory cytokine interleukin (IL) 1in the development of inflammatory responses and structural mediobasal TLE with hippocampal sclerosis.Objective: to study the association of the carriage of the SNPs rs16944 and rs1143634 in the IL-1B gene and rs6265 in the BDNF gene with the development of TLE.Patients and methods. Real-time polymerase chain reaction was used to conduct a molecular genetic study of the carriage of the SNPs rs1143634 and rs16944 in the IL-1B gene and rs6265 in the BDNF gene in 84 patients with TLE and in 203 healthy Caucasian volunteers, who lived in the Siberian Federal District.Results and discussion. The carriage of the high-producing C allele (odds ratio (OR)=2.01; 95% confidence interval (CI), 1.31–3.08; p=0.001) and the homozygous CC genotype (OR=2.48; 95% CI, 1.47–4.17; p=0.001) of SNP rs1143634 in the IL-1B gene was found to be statistically significantly associated with the development of TLE in the examined population. There were no statistically significant differences in the carriage of the SNPs rs1143634 and rs16944 in the IL-1B gene and rs6265 in the BDNF gene with the clinical presentations and course of TLE (p>0.05). The carriage of the SNP rs6265 in the BDNF gene was ascertained to be unassociated with the development of TLE (2=0.3; p =0.86).Conclusion. The authors have established an association of the carriage of the high-producing C allele and the homozygous CC genotype of the SNP rs1143634 in the IL-1B gene with TLE.